Training for citizenship and intercultural dialogue in the National Cross-Cultural Bilingual Education Plan - Carrascal Pretell, Julio (2020)
This work looks into the main document of the National Cross-Cultural Bilingual Education Plan (PNEIB in Spanish) 2021 in Peru. This educational proposal highlights the revaluation of native languages, citizenship training and cross-cultural dialogue among the various social agents linked to the project. Thus, this research studies each of the above three issues to account for their effective implementation based on the discourse analysis of the program. For this purpose, the critical inter-culturality proposal, the abilities approach and the human capital development perspective are used. We then analyze if the project formulated by the PNEIB is viable only at discourse level or has an effective correlation in the implementation of this education policy.